Problems faced by newly graduated musicians to get a job in the music industry / Othniel Luke Suinggi - Suinggi, Othniel Luke (2013)
The aim of this research was to identify the problems faced by newly graduated musicians to get a job in the music industry, the effects towards newly graduated musicians and also the ways to overcome the problems to get ajob in the music industry. A set of questionnaire were distributed to 50 newly graduated musicians and returned. The results on this study gave a lot of insights and information based on the objectives of this study. Based on the data collected, the problems faced by newly graduated musicians occurs because of not able to play their major instrument well as well as sight reading, socializing skills to build a good connection and also the lack of experience to perform well on stage